Cohort differences in adult-life trajectories of internal and external control beliefs: a tale of more and better maintained internal control and fewer external constraints - Gerstorf, Denis; Drewelies, Johanna; Duezel, Sandra; Smith, Jacqui; Wahl, Hans-Werner; Schilling, Oliver; Kunzmann, Ute; Siebert, Jelena Sophie; Katzorreck, Martin; Eibich, Peter; Demuth, Ilja; Steinhagen-Thiessen, Elisabeth; et al. (Psychology and aging, 2019)
Life Span theory posits that sociohistorical contexts shape individual development. In line with this proposition, cohort differences favoring later-born cohorts have been widely documented for cognition and health. However, little is known about historical change in how key resources of psychosocial functioning such as control beliefs develop in old age. We pooled data from 3 independent samples: Berlin Aging Study (6 waves, N = 414); Interdisciplinary Longitudinal Study of Adult Development (4 waves, N = 925); and Berlin Aging Study II (4 waves, N = 1,111) to construct overlapping multiyear longitudinal data from ages 61 through 85 years for cohorts born 1905 to 1953 and examine historical changes in within-person trajectories of internal and external control beliefs. Results revealed that earlier-born cohorts exhibit age-related declines in internal control beliefs regarding both desirable and undesirable outcomes, whereas later-born cohorts perceive higher internal control and maintain this advantage into old age. Earlier-born cohorts also experience steep age-related increases in external control beliefs regarding both powerful others and chance, whereas later-born cohorts perceive lower external control and were stable across old age. Education and gender disparities in control beliefs narrowed over historical time. Sociodemographic, physical health, cognitive, and social factors explained some of the differences in control beliefs, and accounted for sizable portions of cohort effects. Our results indicate that current generations of older adults perceive more and better maintained internal control and fewer external constraints. We discuss potential underlying mechanisms and consider conceptual and societal implications of our findings. (APA PsycInfo Database Record (c) 2019 APA, all rights reserved)
Gesehen am 04.03.2020